Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Ulang Dengan Kepuasan Konsumen Sebagai Variabel Intervening pada Gapyeong Korean BBQ Setia Budi Medan - Rahel Olivia Marpaung; Safelya Sigalingging; Apren Halomoan Hutasoit; Purnaya Sari Tarigan (Universitas Methodist Indonesia, 2024)
The study aims to find out the impact of brand image and price on customer satisfaction re-purchase decisions as an intervening variable on Gapyeong Korean BBQ. This research uses a quantitative method of causal research with primary data taken from the dissemination of the questionnaire. The sample used in this study was 100 respondents who made a purchase at Gapyeong Korean BBQ. This study uses a non-probability sampling technique, namely purposive sampling using the Slovin formula. Slovin is a formula used to find large samples that are estimated to represent the entire population. The data analysis technique in this study uses (SEM) structural equation modeling using the help of smart-PLS to solve the formula problems and hypotheses that have been formulated in this research as well as used to test the relationship between variables. The results of this study showed that brand image did not have a significant impact on consumer satisfaction, price had a significant influence on cosmopolitan satisfaction, brand image had no significant effect on re-purchase decisions, price did not significantly influence re-purchase decisions, customer satisfaction had no significant impact on resupply decisions, consumers satisfaction could not mediate the influence of brand image variables on resumption decisions, and consumers satisfaction couldn’t mediate price on resuspension decisions